Changes In Special Items And Future Firm Growth - Shin, Young Zik; Lee, Yong Gyu (Journal of Applied Business Research, 2017)
This study examines the effect of changes in special items on future firm growth. We find that a decrease in special items reverses almost completely through one-year-ahead earnings, whereas an increase in special items is positively associated with the next year’s earnings growth. We also find that the information embedded in changes in special items is incremental to that of fundamental signals documented in the literature, thereby identifying changes in special items as an additional fundamental signal. Furthermore, we find that both an increase and a decrease in special items lead to decreases in future sales and net operating assets, suggesting an inverse U-shaped relation between changes in special items and growth in these measures. Overall, our findings underscore the importance of considering various growth measures in understanding the implication of changes in special items for future firm growth.